Knowledge of Gender-Based Violence among College Students of Kathmandu, Nepal - Karki, Tej Bahadur; Rawal, Bhagyashree (Nepal Journal of Multidisciplinary Research, 2022)
Gender-based violence is harmful to the personal and professional growth of every victim, so it should be abolished from society. The students can be the change-maker in society so the study assessed the knowledge of college students about gender-based violence. The study was based on a quantitative design. A total of 120 students, aged from 16 to 20 years, were included in the study. The structured survey questionnaire was used to collect the data. The frequency distribution and Chi-square test were used to analyze the data. The findings show that in total 98.3% of youth heard about GBV. All students were aware of physical violence, 96.6% male and 100% female were aware of sexual violence, and 79.3% male and 100% female were aware of psychological violence. There was no significant association between male and female students regarding their knowledge of GBV because the p-value of the Chi-square test was greater than the .05 significant level. In conclusion, more female students were aware of the nature and types of violence than male students. Similarly, more female students used to talk about the violence with their friends than friends. Though, statistically, there were no differences in knowledge of male and female students about gender-based violence. The future researcher can study the experience of gender-based violence among college students.